Differentiation of exhausted CD8+ T cells after termination of chronic antigen stimulation stops short of achieving functional T cell memory - Tonnerre, Pierre; Wolski, David; Subudhi, Sonu; Aljabban, Jihad; Hoogeveen, Ruben C.; Damasio, Marcos; Drescher, Hannah K.; Bartsch, Lea M.; Tully, Damien C.; Sen, Debattama R.; Bean, David J.; Brown, Joelle; et al. (Nature immunology, 2021)
T cell exhaustion is associated with failure to clear chronic infections and malignant cells. Defining the molecular mechanisms of T cell exhaustion and reinvigoration is essential to improving immunotherapeutic modalities. Here we confirmed pervasive phenotypic, functional and transcriptional differences between memory and exhausted antigen-specific CD8 + T cells in human hepatitis C virus (HCV) infection before and after treatment. After viral cure, phenotypic changes in clonally stable exhausted T cell populations suggested differentiation toward a memory-like profile. However, functionally, the cells showed little improvement, and critical transcriptional regulators remained in the exhaustion state. Notably, T cells from chronic HCV infection that were exposed to antigen for less time because of viral escape mutations were functionally and transcriptionally more similar to memory T cells from spontaneously resolved HCV infection. Thus, the duration of T cell stimulation impacts exhaustion recovery, with antigen removal after long-term exhaustion being insufficient for the development of functional T cell memory. Lauer and colleagues examine CD8 + T cells following cure of human hepatitis C virus (HCV) infection. CD8 + T cells exposed to chronic HCV-specific activation show durable functional, phenotypic and transcriptional exhaustion that is maintained even after antigen stimulus is removed.